A Comparative Study on Outcome of Ileostomy versus Colostomy for Temporary Decompression of Colorectal Anastomosis (The Planet, 2021)
Background: The use of loop ileostomy or loop transverse colostomy represents an important issue in colorectal surgery. The rate as well as the clinical outcome of anastomotic leakage in colorectal anastomosis necessitates a loop stoma for fecal diversion. The aim of this study was to determine the outcome of loop transverse colostomy compared to loop ileostomy as a temporary defunctioning stoma following colorectal surgery with colorectal anastomosis. Objectives: To find out the outcome of ileostomy versus colostomy for temporary decompression of colorectal anastomosis. Study Design: It was a prospective observationalstudy. Place of study: Sher-E-Bangla Medical College Hospital, Barisal .Result: In this study total number of patients 60, female were more in colostomy group. Median age was 62¬±¬¬¬¬12 years in ileostomy group and 64±14 years in colostomy group. . The two groups (IL, CL) were more or less similar to primary pathology where carcinoma rectum is the leading cause. The time of first stoma action is 2 days in ileostomy group and 4.5 days in colostomy group. There was a highly significant difference / etween the groups in the interval from stoma construction and its subsequent first action (